2019
DOI: 10.3390/en12142692
|View full text |Cite
|
Sign up to set email alerts
|

Electric Vehicle Charging Load Forecasting: A Comparative Study of Deep Learning Approaches

Abstract: Load forecasting is one of the major challenges of power system operation and is crucial to the effective scheduling for economic dispatch at multiple time scales. Numerous load forecasting methods have been proposed for household and commercial demand, as well as for loads at various nodes in a power grid. However, compared with conventional loads, the uncoordinated charging of the large penetration of plug-in electric vehicles is different in terms of periodicity and fluctuation, which renders current load f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 46 publications
1
80
0
Order By: Relevance
“…GRU model using 1 hidden layer provided the best performance with normalized RMSE (NRMSE) of 2.89%. Other studies [87] have looked at even higher resolution of time series data, and provided EV charging load forecasting for super short term (minutely data). A comparative study of various DL models showed that LSTM performs better than conventional ANNs by reducing the forecasting error by more than 30%.…”
Section: Deep Learning For Analysis and Prediction Of Charging Behmentioning
confidence: 99%
“…GRU model using 1 hidden layer provided the best performance with normalized RMSE (NRMSE) of 2.89%. Other studies [87] have looked at even higher resolution of time series data, and provided EV charging load forecasting for super short term (minutely data). A comparative study of various DL models showed that LSTM performs better than conventional ANNs by reducing the forecasting error by more than 30%.…”
Section: Deep Learning For Analysis and Prediction Of Charging Behmentioning
confidence: 99%
“…The deep learning algorithm has the characteristics of information memory, self-learning, optimization calculation, etc. It also has strong computing power, complex mapping ability, and various intelligent processing capabilities [25].…”
Section: Motivation and Problem Statementmentioning
confidence: 99%
“…A comparison of different approaches was also possible. For super-short-term forecasting with deep learning, the long-short-term memory (LSTM) already showed very realistic results as described in [5].…”
Section: Introductionmentioning
confidence: 97%